Pengaruh Motivasi, Lingkungan Kerja dan Displin Kerja Terhadap Kinerja Karyawan Pamella Dua Yogyakarta - Wati, Disya Fitri Naris; Nurwahyudi, Muhammad Robi (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study is useful to test and determine the effect of motivation, work environment, and work discipline on employee performance Pamella Dua Yogyakarta. This research uses a method that is quantitative with a nonprobility sample sample. The population of 50 respondents who are all employees of Pamella Dua Yogyakarta. The use of samples in this study amounted to 44 respondents. Using data analysis with multiple linear regression methods. The results of the T test research explain that motivation has a positive and significant effect on the performance of Pamella Dua Yogyakarta employees, the work environment has a positive and significant effect on the performance of Pamella Dua Yogyakarta employees, and work discipline has a positive and insignificant effect on the performance of Pamella Dua Yogyakarta employees. From the F test where this study obtained the results of F count 28.904> F table 2.83l with significant results of 0.05 indicates that motivation, work environment and work discipline together have an influence on employee performance Pamella Dua Yogyakarta.